Karnataka Annual Plan 1981-82 Volume-I Review of Planning and Proposals for the Annual Plan - Planning Commission (Planning Commission, 1981)
1980-81, being the first year of the New Sixth Five Year Plan of the State for the period 1980-85, it is appropriate to assess the performance dining the first year in term of the development outlay and performance. Table-1.1 indicates the budgeted and anticipated expenditure of State Plan for 1980-81 vis-a-vis the proposed 1980-85 Plan Outlay.
Government of Karnataka, Planning Department